From hard work to grit: On the discursive formation of talent - Kilger, M. (Scandinavian Sport Studies Forum, 2019)
This article examines the long historical interest for the selection of young talented children in sports. This seemingly everlasting search for talents and the quest for the especially gifted is followed by the practice of trying to find and select the right individuals. This paper elucidates historical representations of talent and talent selection in a series of professional sports literature in Sweden during the 1930s, 1980s, 1990s and 2010s.